RUQYAH SEBAGAI METODE PENGOBATAN BERBASIS SPIRITUAL: (Studi Metode Ruqyah di Jam’iyyah Ruqyah Aswaja Tulungagung) - Zein, Muhammad Khafid Zulfahmi (Hisbah: Jurnal Bimbingan Konseling dan Dakwah Islam, 2022)
Islam is a religion brought by the Prophet Muhammad SAW as a mercy that not only guides his people but also it must provides various solutions to every problem in human life. Especially in terms of health which is a hereditary problem until now, many Islamic scientists were born and known to the world for discovering treatment methods such as Ibn Sina as the father of World Medical Scientists. Alternative medicine method ruqyah of TulungagungThis articles aim to explain how the symbolic interaction built by raqy to patients and the community up to this modern era, a method that is trusted by the community with its spiritual approach at Jam’iyyah Ruqyah Aswaja Tulungagung, this study uses a qualitative method with a phenomenological approach belonging to Rudolf Otto, namely Misterium Tremendum et Fascinans which is juxtaposed with the theory of symbolic interaction. The data collection technique used in this paper is an interview with three sources, namely; JRA Tulungagung, patients and the general public, observation, and documentation. JRA is an organization affiliated to Nahdlatul Ulama and stands not only as alternative medicine but also preaching in the fight against Wahabi ideologi. Keywords: Ruqyah, Religion, Alternative medicine